Business model innovation and strategy making nexus: evidence from a cross‐industry mixed‐methods study. (17th January 2015) - Cortimiglia, Marcelo Nogueira; Ghezzi, Antonio; Frank, Alejandro Germán
Abstract : Theory discussing how to define and frame the relationship between the strategy making process (SMP) and business model innovation (BMI) is still incipient in the academic literature. Thus, this study aims at investigating the relationship between SMP and BMI by addressing (1) when firms engage in BMI within the overall SMP, and (2) how firms design a new business model (BM) or improve their current BM within the overall SMP. The research questions are tackled by means of a mixed‐method research, combining (1) a quantitative survey on 138 firms involved in SMP and BMI (to understand when BM design and improvement occur) and (2) a qualitative multiple‐case study focused on four firms (to address how BM design and improvement evolve). The findings empirically validate the arguments that BM design and improvement are more likely to be positioned in the strategic alternatives implementation step of the SMP, and BM is related to strategy execution; on top of this, light is shed on the inherent dynamics of the BMI process for different types of BMI.